Pengaruh Gaya Kepemimpinan, Lingkungan dan Motivasi terhadap Kepuasan Kerja Guru di SMK Negeri Jakarta Utara - Virgana Virgana; Didi Suprijadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
This causal research is aimed at obtaining information related to the possibility that the teachers’ job satisfaction of the government vocational schooll in North of Jakarta is effected by leadership style, work environment, and teachers’ work motivation. Research has been implemented using path analysis after all variables put into a matrix of correlation. In this research, teachers has been chosen as a unit analysis and 100 samples selected randomly. The results of analysis finds out that: 1) the teachers’ work motivation is affected directly by leadership style; 2) ) the teachers’ work motivation is affected directly by work environment; 3) the teachers’ job satisfaction is affected directly by leadership style; 4) the teachers’ job satisfaction is affected directly by work environment;5) the teachers’ job satisfaction is affected directly by the teachers’ work motivation; 6) the teachers’ job satisfaction is affected indirectly by leadership style; and 7) the teachers’ job satisfaction is affected indirectly by work environment. Therefore, the leadership style, work environment, and teachers’ work motivation should be put into account of human resources development in managing the teachers’ job satisfaction at The Education Office of DKI Jakarta Province.